Brain responses to morphologically complex verbs: An electrophysiological study of Swedish regular and irregular past tense forms. (August 2019) - Schremm, Andrea; Novén, Mikael; Horne, Merle; Roll, Mikael
Abstract: The present electrophysiological study investigated irregular versus regular verb form processing in Swedish during reading. In line with previous results from other languages, overregularized verbs, i.e. incorrect irregular stem + regular past tense suffix combinations (e.g. * stjäl + de 'steal + past tense'), elicited a left-lateralized negativity (LAN) relative to correct irregulars ( stal 'stole'), suggesting rule-based decomposition of regularly inflected words. Lack of a similar effect for misapplication of the irregular stem formation pattern on regular verbs (e.g. * löft 'lifted' instead of lyfte ) suggests the involvement of different processing mechanisms, possibly whole word access, for irregular items, at least to some degree. A P600 showing reprocessing was seen for all incorrect forms. The results add cross-linguistic support for morphological decomposition in the verbal inflection of a language where results from previous neurolinguistic studies of nominal inflection have only suggested the use of full-form access to words. Highlights: ERPs of both overregularized and irregularized verbs in Swedish were recorded. LAN obtained for overregularized verbs suggests rule-based decomposition. Irregularized verbs elicited only a P600 relative to the correct variant.